Effect of nutrients deficiency on biofilm formation and single cell protein production with a purple non-sulphur bacteria enriched culture - S. Shaikh (17337769) (2023)
Purple non-sulphur bacteria (PNSB) are of interest for biorefinery applications to create biomolecules, but their production cost is expensive due to substrate and biomass separation costs. This research has utilized fuel synthesis wastewater (FSW) as a low-cost carbon-rich substrate to produce single-cell protein (SCP) and examines PNSB biofilm formation using this substrate to achieve a more efficient biomass-liquid separation. In this study, PNSB were grown in Ca, Mg, S, P, and N-deficient media using green shade as biofilm support material. Among these nutrient conditions, only N-deficient and control (nutrient-sufficient) conditions showed biofilm formation. Although total biomass growth of the control was 1.5 times that of the N-deficient condition and highest overall, the total biofilm-biomass in the N-deficient condition was 2.5 times greater than the control, comprising 49% of total biomass produced. Total protein content was similar between these four biomass samples, ranging from 35.0 ± 0.2% to 37.2 ± 0.0%. The highest protein content of 44.7 ± 1.3% occurred in the Mg-deficient condition (suspended biomass only) but suffered from a low growth rate. Overall, nutrient sufficient conditions are optimal for overall protein productivity and dominated by suspended growth, but where fixed growth systems are desired for cost-effective harvesting, N-deficient conditions provide an effective means to maximize biofilm production without sacrificing protein content. Other Information Published in: Biofilm License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.bioflm.2022.100098